Primeira Ocorrência de Aedes (Stegomyia) albopictus (Skuse) no Estado de Sergipe - Santana, Antônio César da Silva; Dantas de Araujo, Catarina Zita; Novaes, José Rocha Prudente de; Santos, Maria da Glória Mendes dos; Santana, Waltemir Souza (EntomoBrasilis, 2014)
O mosquito Aedes (Stegomyia) albopictus (Skuse), vetor de várias arboviroses, foi registrado pela primeira vez no estado de Sergipe, Brasil, no município de Areia Branca, localizado no centro-leste, nas coordenadas 10°45'29”S e 37°18'45”W e a 36 km da capital Aracaju. A primeira larva de Ae. albopictus foi coletada na 32ª semana epidemiológica de 2011, no Povoado Terra Preta de Cima durante as atividades de Controle de Qualidade do Programa de Controle da Febre Amarela e da Dengue (PCFAD). Mais tarde, na 50ª semana epidemiológica de 2012, foi encontrada mais uma larva de Ae. albopictus, desta vez no Povoado Manilha de Baixo. Em seguida, no Povoado Garangau (10º44'55”S e 37º29'40”W) a 28 km da sede do município de Campo do Brito foram capturadas três larvas e duas pupas de Ae. albopictus durante revisão semanal de amostras do PCFAD, ou seja, na 47ª semana epidemiológica de 2012. Dessa forma, procuramos mostrar a importância do Controle de Qualidade para os Programas de Controle de Endemias nos estados e no Brasil, visando à efetivação de providências rápidas e eficientes para a prevenção e o controle de doenças veiculadas por mosquitos. First Occurrence of Aedes (Stegomyia) albopictus in the State of Sergipe, Brazil Abstract. The mosquito Aedes (Stegomyia) albopictus (Skuse), a vector for several arboviral diseases, was recorded for the first time in the state of Sergipe, Brazil, in the municipality of Areia Branca, located in the central-eastern part of the state at the coordinates 10°45'29"S and 37°18'45"W and 36 km from the state capital, Aracaju. The first larva of Ae. albopictus was collected in the 32nd epidemiological week of 2011, in the settlement of Terra Preta de Cima and was identified systematically in the Central Public Health Laboratory (LACEN-SE) during quality control activities within the yellow fever and dengue control program (PCFAD). In the 50th epidemiological week of 2012, another larva of Ae. albopictus was found, this time in the settlement of Manilha de Baixo. In the neighboring municipality of Campo do Brito, three larvae and two pupae of Ae. Albopictus were found in the settlement of Garangau (10º44'55"S and 37º29'40"W), 28 km from the main center of the municipality. As in the abovementioned records, systematic identification was only made at a late stage, given that the samples from the 47th epidemiological week of 2012 arrived at LACEN/SE in January, 2013. This technical note serves alert public health managers to the importance of quality control for endemic disease control programs, with the aim of effecting rapid and efficient control and prevention measures for mosquito-borne diseases.